Numerical Analysis of Machine Foundation Resting Saturated Sandy Soil - Mohammed Y. Fattah; Nahla M. Salim; Wourood T. Al-Shammary (Engineering and Technology Journal, 2014)
The behavior of machine foundation on saturated porous medium can be considered as a complicated geotechnical problem due to nature of dynamic loads and plasticity of soil which make the analysis and design of foundation subjected to dynamic loads more complex. The main criteria for safe performance of machine foundations subjected to dynamic loads are to control excessive displacements. In this paper, a dynamic analysis of strip machine foundation with multiple thicknesses is placed at the middle of the top surface of saturated sand with different states (i.e. loose, medium and dense), and vertical harmonic excitation is carried out and building up of the excess pore water pressure. The dynamic analysis is performed numerically by using finite element software, PLAXIS 2D. The soil is assumed as elastic perfectly plastic material obeys Mohr-Coulomb yield criterion. A parametric study is carried out to evaluate the dependency of machine foundation on various parameters including the amplitude and the frequency of the dynamic load. The dynamic response (displacement and excess pore water pressure) generally increases with increasing of loading amplitude, but the displacement and excess pore water pressure versus frequency are not smooth and exhibit undulations (peaks and troughs).